Growth factors, their receptors and down-stream signaling proteins in human tumors: from experiment to clinical practice - E. S. Gershtein; N. E. Kushlinsky (Успехи молекулярной онкологии, 2015)
The basic contemporary data and the results of authors’ long-term personal research devoted to the role of auto / paracrine growth factors, their receptors and some down-stream signaling proteins (PI3K, Akt, NF-κB) in clinical course, prognosis and development of hormonal and drug sensitivity of various human tumors are reviewed. The data on the key targeted drugs suppressing various growth factor signaling pathways components are summarized with special attention to the criteria of assessment of individual sensitivity to these drugs including those based on modern molecular biologic technologies.